1993
DOI: 10.1136/pgmj.69.815.735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of octreotide on circulating islet B cell products in endogenous hyperinsulinism

Abstract: Summary:The role of somatostatin analogues in the medical management of insulinomas is unclear. We describe an elderly patient with clinical and biochemical features of endogenous hyperinsulinism attributable to a benign islet B cell disorder whose incapacitating neuroglycopaenic symptoms responded dramatically to octreotide 50 pg subcutaneously at 2200 h each night. Octreotide suppressed inappropriate plasma concentrations ofinsulin thereby preventing fasting hypoglycaemia. Fasting concentrations of proinsuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Another case of endogenous hyperinsulinism caused by a benign b-cell disorder but not insulinoma, in which hypoglycemia was successfully controlled by 50 mg of octreotide once daily, was also an 80-year-old man [21]. Although the metabolism and excretion of octreotide has not been investigated in detail, a preliminary study reported that hepatic extraction of octreotide was estimated to be between 30 and 40% in healthy volunteers [20].…”
Section: Discussionmentioning
confidence: 99%
“…Another case of endogenous hyperinsulinism caused by a benign b-cell disorder but not insulinoma, in which hypoglycemia was successfully controlled by 50 mg of octreotide once daily, was also an 80-year-old man [21]. Although the metabolism and excretion of octreotide has not been investigated in detail, a preliminary study reported that hepatic extraction of octreotide was estimated to be between 30 and 40% in healthy volunteers [20].…”
Section: Discussionmentioning
confidence: 99%